ANALYSIS OF THE ROLE OF RUGEMUK MANDIRI VILLAGE-OWNED ENTERPRISES (BUMDES) IN THE PROVISION OF CLEAN WATER IN RUGEMUK VILLAGE, LABU BEACH, DELI SERDANG - Safira, Putri; Nanda, Meutia; Elvina, Elvina; Salsabilla, Salsabilla; Anggraini, Riri (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
The provision of clean water in Indonesia's coastal areas is a serious challenge considering the limited water resources that are vulnerable to seawater pollution and intrusion. Rugemuk Village, on Labu Beach, Deli Serdang, is one of the coastal areas that faces the problem of access to clean water. In this context, Rugemuk Mandiri Village-Owned Enterprises (BUMDes) was established in 2017 to manage the supply of clean water effectively and sustainably. The purpose of this research is to analyze the role of Rugemuk Mandiri Village-Owned Enterprises (BUMDes) in providing clean water in Rugemuk Village, Labu Beach, Deli Serdang. This study uses a qualitative descriptive approach with interview techniques for the four main groups of respondents, namely the director of BUMDes, village heads, hamlet heads, and the community of Rugemuk Village with a total of 6 respondents. This study shows that BUMDes Rugemuk Mandiri has succeeded in providing clean water for the people of Rugemuk Village. BUMDes manages the distribution of clean water through a piping system by utilizing four drilled wells spread across four hamlets, affordable tariff management, and a meter-based payment system. There are still challenges related to clean water supply services from some communities, as well as the need to expand the reach of clean water services to housing that has not been connected to the clean water supply program. It is hoped that BUMDes will further improve water quality monitoring and expand the reach of clean water services by developing infrastructure. To increase the role of BUMDes in the provision of clean water, it is necessary to increase in routine water quality monitoring, encourage active community participation and expand the reach of clean water services.